Several pathways involved in cardiac fibrosis which helps to discover better treatment (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Cardiac fibrosis is abnormal accumulation of extracellular matrix and collagen in myocardial tissues. It is major reason of progression of heart failure, so its prevention and treatment is main aim for curing heart failure. The objective of this review is to discuss the pathways and several mechanisms at molecular level which may involve in cardiac fibrosis. Dynamic network of fibrillar collagen, glycoprotein, proteoglycans and other main bio molecules represents ECM, where its regulation controlled by various components synthesis and degradation. The collagen network gives Support and alignment of myocyte blood vessels and lymphatic vessels, relative to one another thereby preserving myocardial thickness and architecture. Some stem cells therapy helps in cardiac fibrosis. Ang II stimulation increases mRNA and protein expression by cardiomyocytes and cardiac fibroblasts. TGF-β with RAS system increases progression of cardiac fibrosis.